Pencarian Kembali Moderasi Beragama Dalam Kitab Itḥāf Al-Dhaki - Senata Adi Prasetia (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2022)
This article explores the concept of religious moderation in the Kitab Itḥāf al-Dhaki and its relevance in contemporary Indonesian Islam. As a new national policy, religious moderation is open to criticism for conceptual establishment. This policy aims for addressing the threat of religious extremism and intolerance in Indonesia which has become more active over the past two decades. Also, have been a move to curb the political exploitation of religion which has led to identity politics and hate speech flourishing in the 2019 elections. By using a qualitative type of research based on a literature study, i.e. the Kitab Ithaf al-Dhaki, this article results that remaking of religious moderation in this manuscript is accommodating two streams of thought is more important than choosing one of them, as long as it can be done. The meaning of moderation according to Ibrahim al-Kurani, author of the Kitab Ithaf al-Dhaki, is a someone who can combine the two meanings of the Qur'an both esoteric and exoteric (i.e., a perfect man or insan kamil). Furthermore, Al-Kurani in Kitab Itḥāf al-Dhaki argues to be moderate, one should be understand both (esoteric and exoteric) thoughts. It's impossible to moderate if you don't know the two streams of thought.. (Artikel ini mengeksplorasi konsep moderasi beragama dalam Kitab Itḥāf al-Dhaki dan relevansinya bagi Islam Indonesia kontemporer. Sebagai kebijakan nasional baru, moderasi beragama terbuka untuk dikritisi demi pematangan konseptual. Terlebih, tujuan dari moderasi beragama adalah untuk mengatasi ancaman ekstremisme dan intoleransi agama di Indonesia yang semakin aktif selama dua dekade terakhir. Selain itu, juga merupakan langkah untuk mengekang eksploitasi politik agama yang telah menyebabkan politik identitas dan ujaran kebencian berkembang dalam pemilu 2019 silam. Dengan menggunakan jenis penelitian kualitatif berbasis studi pustaka, artikel ini menghasilkan temuan bahwa pencarian kembali moderasi beragama dalam manuskrip ini adalah mengakomodir dua aliran pemikiran berseberangan daripada memilih salah satunya, dengan syarat memahami betul kedua aliran pemikiran tersebut. Makna moderasi menurut Ibrahim al-Kurani adalah seseorang yang dapat memadukan dua makna al-Qur’an, baik yang esoteris maupun yang eksoteris (itulah manusia yang sempurna/insan kamil). Lebih lanjut, Al-Kurani dalam Itḥāf al-Dhaki berpendapat untuk menjadi moderat, seseorang harus memahami kedua pemikiran (esoteris dan eksoteris). Tidak mungkin memoderasi jika orang tersebut tidak mengetahui dua aliran pemikiran). Dalam konteks ini, pencarian jati diri moderasi beragama melalui Ithaf al-Dhaki menjadi keniscayaan demi kedewasaan beragama di Islam Indonesia kontemporer.)